A Heuristic Algorithm that Finds the Minimum and the Maximum of the Outputs of a Fuzzy Socio-political Model of E-democracy (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Most of the techniques of nonlinear optimization assume the existence of a differential function, but there also exist other approaches. In this paper, we propose a non-differential algorithm that solves the problem of minimization and maximization for any objective function of several unknown variables. The algorithm searches for a solution vector of variables that yields the optimal result of the objective function, using a trial-and-error process. The algorithm is not fast, but it converges to a non-trivial solution, if it exists. The method will be used to determine the minimum and the maximum of the outputs of a socio-political model of E-Democracy. This model of E-Democracy is based on a Mamdani fuzzy inference system.Â  We provide formalization and Matlab implementation for our fuzzy system and for the algorithm